STROCSS 2019 Guideline: Strengthening the reporting of cohort studies in surgery. (December 2019) - ,; Beamishaj,; Bashashati, Mohammad; Millham, Frederick H.; Orgill, Dennis P.; Noureldin, Ashraf; Nixon, Iain James; Alsawadi, Abdulrahman; Bradley, Patrick J.; Giordano, Salvatore; Laskin, Daniel M.; Basu, Somprakas; et al.
Abstract: Introduction: The STROCSS guideline was developed in 2017 to improve the reporting quality of observational studies in surgery. Building on its impact and usefulness, we sought to update the guidelines two years after its publication. Methods: A steering group was formed to review the existing guideline and propose amendments to the 17-item checklist. A Delphi consensus exercise was utilised to determine agreement across a list of proposed modifications to the STROCSS 2017 guideline. An expert panel of 46 surgeons were invited to assess the proposed updates via Google Forms. Results: The response rate was 91% (n = 42/46). High agreement was reached across all the items and the guideline was finalised in the first round. The checklist maintained 17-items, with modifications primarily considered to improve content and readability. Conclusions: The STROCSS 2019 guideline is hereby presented as a considered update to improve reporting of cohort, cross-sectional and case-control studies in surgery. Highlights: Over 80% response rate on update. Updated STROCSS 2019 guideline has over 70% consensus on all items in first round. Updated STROCSS 2019 guideline has been improved for content and readability.